You are on page 1of 4

Possible derivation:

d/dx(x/(5+2 x)+4 x^5)


Differentiate the sum term by term and factor out constants:
= 4 (d/dx(x^5))+d/dx(x/(5+2 x))
Use the power rule, d/dx(x^n) = n x^(n-1), where n = 5: d/dx(x^5) = 5 x^4:
= d/dx(x/(5+2 x))+4 5 x^4
Simplify the expression:
= 20 x^4+d/dx(x/(5+2 x))
Use the quotient rule, d/dx(u/v) = (v ( du)/( dx)-u ( dv)/( dx))/v^2, where u = x and v = 2 x+5:
= 20 x^4+((2 x+5) d/dx(x)-x d/dx(5+2 x))/(2 x+5)^2
The derivative of x is 1:
= 20 x^4+(-(x (d/dx(5+2 x)))+1 (5+2 x))/(5+2 x)^2
Simplify the expression:
= 20 x^4+(5+2 x-x (d/dx(5+2 x)))/(5+2 x)^2
Differentiate the sum term by term and factor out constants:
= 20 x^4+(5+2 x-d/dx(5)+2 d/dx(x) x)/(5+2 x)^2
The derivative of 5 is zero:
= 20 x^4+(5+2 x-x (2 (d/dx(x))+0))/(5+2 x)^2
Simplify the expression:
= 20 x^4+(5+2 x-2 x (d/dx(x)))/(5+2 x)^2
The derivative of x is 1:
= 20 x^4+(5+2 x-1 2 x)/(5+2 x)^2
Simplify the expression:
Answer: |
| = 20 x^4+5/(5+2 x)^2

Possible derivation:
d/dx(x/(4+2 x)+3 x^4)
Differentiate the sum term by term and factor out constants:
= 3 (d/dx(x^4))+d/dx(x/(4+2 x))
Use the power rule, d/dx(x^n) = n x^(n-1), where n = 4: d/dx(x^4) = 4 x^3:
= d/dx(x/(4+2 x))+3 4 x^3

d/dx(x/(4+2 x)+3x^4)

Simplify the expression:


= 12 x^3+d/dx(x/(4+2 x))
Use the quotient rule, d/dx(u/v) = (v ( du)/( dx)-u ( dv)/( dx))/v^2, where u = x and v = 2 x+4:
= 12 x^3+((4+2 x) (d/dx(x))-x (d/dx(4+2 x)))/(4+2 x)^2
The derivative of x is 1:
= 12 x^3+(-(x (d/dx(4+2 x)))+1 (4+2 x))/(4+2 x)^2
Simplify the expression:
= 12 x^3+(4+2 x-x (d/dx(4+2 x)))/(4+2 x)^2
Differentiate the sum term by term and factor out constants:
= 12 x^3+(4+2 x-d/dx(4)+2 (d/dx(x)) x)/(4+2 x)^2
The derivative of 4 is zero:
= 12 x^3+(4+2 x-x (2 (d/dx(x))+0))/(4+2 x)^2
Simplify the expression:
= 12 x^3+(4+2 x-2 x (d/dx(x)))/(4+2 x)^2
The derivative of x is 1:
= 12 x^3+(4+2 x-1 2 x)/(4+2 x)^2
Simplify the expression:
Answer: |
| = 12 x^3+4/(4+2 x)^2

d/dxf(x)=

d/dx((sqrt(x)/3x+4)

+ 2x2)
=d/dx(x3x+4)+2ddx(x2)
=22x+(3x+4)d/dx(x)d/dx(3x+4)sqrt(x)/(3x+4)2
=12x(3x+4)3x(3x+4)2+4x
=3x+42x3x(3x+4)2+4x
Alternative result:

=12x(3x+4)3x(3x+4)2+4x

f(x) = (x/(3x+4)) + 2x

we then figure out what our derivatives will look like we have two which need solved (and since one is a
2
simple one (the d/dx(x/3x+4) and the second is simply the d/dx(2x )
2
but realize that that to get the derivative of the (x/3x+4) we need to use the quotient rule the (2x ) is very
2
basic derivatives we did first in the unit - so: f(x) = 2x and the derivative is simply f(x) = 2x

Step A setup the function into its derivative


2

d/dx(x/(3x+4) + d/dx(2x )
Step B perform both derivatives well do the second as its easiest
1)
2)

d/dx(2x ) = f(x) = (2)(2x) = 4x


2
the derivative of the first which uses the quotient rule which is fg fg / g(x)
f(x) = x
f(x) = 1
g(x) = 3x+4
g(x) = 3
f(1)g(3x+4) g(3)f(3) / g
3x+4 3(3) / 9

3x+4 9/9 = 3x+4 / 1 = 3x+4

3)

plug results from 2 and 3 into original f(x) = 3x + 4 + 2x2


f(x) = 3x+4 + 4x = 7x + 4